Challenges and opportunities for manureshed management across U.S. dairy systems: Case studies from four regions. Issue 4 (6th April 2022) - Dell, Curtis J.; Baker, John M.; Spiegal, Sheri; Porter, Sarah A.; Leytem, April B.; Flynn, K. Colton; Rotz, C. Alan; Bjorneberg, David L.; Bryant, Ray B.; Hagevoort, G. Robert; Williamson, Jeb C.; Slaughter, Amalia; et al.
Abstract: The manureshed represents cropland needed to safely assimilate manure nutrients from an animal feeding operation. Dairy manuresheds can be contained on‐farm but may need to involve additional farms that can assimilate excess nutrients. We present case studies reviewing challenges and opportunities to manureshed management in four major dairy‐producing states using available information on local manuresheds. Additionally, geographic information system software was used with data from regulated Minnesota dairies to assess cropland assimilative capacities and transport needs surrounding large dairies. Manureshed requirements vary across regions, but increased import of feed and soil phosphorus accumulation constrain on‐farm manure utilization across the United States. In Minnesota, a growing proportion of Jersey cattle and differences in continuous corn ( Zea mays L.) vs. corn–alfafa ( Medicago sativa L.) rotations contribute to the amount of land needed to absorb dairy manure nutrients. Farm‐gate budgets reveal that N‐based manuresheds can be contained within Idaho dairies, but P‐based manuresheds extend beyond the farm. In New Mexico, relocation of surplus manure nutrients off the farm is common via informal networks, but incentives to strengthen these networks could ensure sustainable manureshed management. Evaluation of manureshed requirements in Pennsylvania is often complicated by the need for additional nutrient management planning and greater understanding of nutrient balances on the preponderance of small dairies. Nutrient imbalances with highly concentrated dairy production often lead to the need for manure transport off‐farm. However, advances in herd and cropland management offer opportunities to improve on‐farm nutrient efficiencies, and emerging networks and technologies promise to facilitate manure export when needed. Core Ideas: Overall, available soil P assimilation capacity is the largest constraint on manureshed management. In Minnesota, crop rotations and dairy breeds affect manureshed areas. In Idaho, up to 80% of dairies have P‐based manuresheds requiring off‐farm export. Groundwater availability in New Mexico challenges long‐term manureshed solutions. Nutrient management on small to medium dairies is Pennsylvania's main challenge.